Interface Engineering Enabled Low Temperature Growth of Magnetic Insulator on Topological Insulator - Nirjhar Bhattacharjee; Krishnamurthy Mahalingam; Alexandria Will‐Cole; Yuyi Wei; Adrian Fedorko; Cynthia T. Bowers; Michael Page; Michael McConney; Don Heiman; Nian Xiang Sun (Advanced Materials Interfaces, 2022)
Abstract Combining topological insulators (TIs) and magnetic materials in heterostructures is crucial for advancing spin‐based electronics. Magnetic insulators (MIs) can be deposited on TIs using the spin‐spray process, which is a unique nonvacuum, low‐temperature growth process. TIs have highly reactive surfaces that oxidize upon exposure to atmosphere, making it challenging to grow spin‐spray ferrites on TIs. In this work, it is demonstrated that a thin titanium capping layer on TI, followed by oxidation in atmosphere to produce a thin TiOx interfacial layer, protects the TI surface, without significantly compromising spin transport from the magnetic material across the TiOx to the TI surface states. First, it is demonstrated that in Bi2Te3/TiOx/Ni80Fe20 heterostructures, TiOx provides an excellent barrier against diffusion of magnetic species, yet maintains a large spin‐pumping effect. Second, the TiOx is also used as a protective capping layer on Bi2Te3, followed by the spin‐spray growth of the MI, NixZnyFe2O4 (NZFO). For the thinnest TiOx barriers, Bi2Te3/TiOx/NZFO samples have antiferromagnetic (AFM) disordered interfacial layer because of diffusion. With increasing TiOx barrier thickness, the diffusion is reduced, but still maintains strong interfacial magnetic exchange‐interaction. These experimental results demonstrate a novel method of low‐temperature growth of magnetic insulators on TIs enabled by interface engineering.